2021
DOI: 10.1073/pnas.2017889118
|View full text |Cite
|
Sign up to set email alerts
|

Early systemic immune biomarkers predict bone regeneration after trauma

Abstract: Severe traumatic injuries are a widespread and challenging clinical problem, and yet the factors that drive successful healing and restoration of function are still not well understood. One recently identified risk factor for poor healing outcomes is a dysregulated immune response following injury. In a preclinical model of orthopedic trauma, we demonstrate that distinct systemic immune profiles are correlated with impaired bone regeneration. Most notably, elevated blood levels of myeloid-derived suppressor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 57 publications
(55 reference statements)
4
35
1
Order By: Relevance
“…Surgical trauma can affect the dynamic changes occurring in PBMCs during the perioperative period. Specifically, surgical trauma activates various stress responses, causing the release of catecholamines, cortisol and inflammatory mediators, 22 which further strengthens the perioperative inflammatory response and immune suppression, 23 , 24 and even leads to immune cell dysfunction, thus triggering changes in PBMCs. 25 Effector B cells may have been the cluster the most affected by surgical trauma in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical trauma can affect the dynamic changes occurring in PBMCs during the perioperative period. Specifically, surgical trauma activates various stress responses, causing the release of catecholamines, cortisol and inflammatory mediators, 22 which further strengthens the perioperative inflammatory response and immune suppression, 23 , 24 and even leads to immune cell dysfunction, thus triggering changes in PBMCs. 25 Effector B cells may have been the cluster the most affected by surgical trauma in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Injury induces an immunological response from acute tissue damage incurred during surgical procedures such as laparotomy, 31 castration, 23 or implantation of a biomaterial. Additionally, inflammation can be induced via bone fracture 40 or creation of segmental bone defects 2 …”
Section: Models Of Injurymentioning
confidence: 99%
“…An additional model involved testing a panel of cells, cytokines, and chemokines to understand the immune response during bone healing in 13‐week‐old Sprague Dawley rats with critically sized (8 mm) femoral defects 2 . Through multivariate analysis of responses in rats receiving either immediate or delayed (at 8 weeks) treatment with bone morphogenetic protein‐2 in alginate hydrogel and a polycaprolactone (PCL) mesh, Cheng et al 2 found B cells, IL‐6, IL‐13, and IL‐1α correlated with successful healing. Additionally, IFN‐γ induced protein‐10 (IP‐10), myeloid‐derived suppressor cells (MDSCs), and cytotoxic T cells were indicative of poor healing.…”
Section: Models Of Injurymentioning
confidence: 99%
See 2 more Smart Citations